Recent advances in development of electroactive composite materials for electrochromic and supercapacitor applications - Mohanadas, Dharshini; Sulaiman, Yusran (Elsevier, 2022)
Supercapacitors are outstanding energy storage devices with remarkable electrochemical properties i.e., enormous specific capacitance, rapid charge/discharge rate, great specific power and long-life cycle. Researchers have been developing the supercapacitor application by including smart functions such as electrochromic. The bifunctional devices with both electrochromic and supercapacitive properties are highly explored as the environmentally friendly supercapacitors are able to depict visual color changes upon applied potential. Hence, the excessive charging issue in the supercapacitors can be overcome and the energy level of the device can be also determined qualitatively, observing the color of the material. Numerous electroactive materials such as carbon-based materials, conductive polymers (CPs), transition metal oxides (TMOs) and metal-organic frameworks (MOFs) have been greatly investigated in supercapacitor applications. This review mainly emphasizes and elaborates on the electrochromic and supercapacitive performance of CP/TMO-, graphene- and MOF-based materials. At the same time, the criteria and the challenges for bifunctional electrochromic supercapacitors are also addressed in this review.